Emotional Freedom Technique for Reducing Depression and Improving Quality Of Life among Stroke Patients in Pakistan: A Randomized Controlled Trial - Shahzadi, Shazia (2024)
Stroke is a significant cause of disability, often leading to psychological distress and impacting the lives of patients and their caregivers, particularly in regions like Pakistan, where traditional rehabilitation primarily focuses on physical recovery, neglecting mental health and psychological rehabilitation. Emotional Freedom Technique (EFT) is an evidence-based practice that is an innovative psychological intervention. This study investigated the feasibility and efficacy of the Emotional Freedom Technique in alleviating depression and enhancing the quality of life (QOL) among stroke patients and assessed the caregiver burden (CGB) in Pakistan. The deductive approach is employed, as EFT is an independent variable. The dependent variables were decreased depression, increased quality of life, decreased Subjective distress units, and reduced caregiver burden. The severity of stroke is a moderator, and mediator variables are coping mechanisms, emotional stability, and comorbidities. In a randomized controlled trial, 100 ischemic stroke patients were enrolled from Pakistan, they were explicitly located in Islamabad and Rawalpindi; five rehab hospitals were short-listed, two from Islamabad and three from Rawalpindi. Patients were allocated equally to EFT intervention, and standard care (Physical rehabilitation) was conducted in control groups. MMSE-U was used to cater to the inclusive criteria. Depression and quality of life were assessed using the Beck Depression Inventory-II (BDI-II-U) and World Health Organization Quality of Life (WHOQOL-U) scale at baseline and post intervention and follow-up with single blinding. Statistical analyses included paired t-tests, independent t-tests and repeated measure ANOVA to evaluate within-group and between group differences. In Post-intervention, the EFT group exhibited significant reductions in depression, BDI-II-U scores (p < 0.01), and notable improvements in quality of life (WHOQOL-U) scores (p < 0.01) compared to the control group, indicating EFT's effectiveness in reducing depression levels and enhancing the quality of life in stroke patients and also decreased the caregiver burden as measured by the BSFC-10 items scale. Integrating EFT into stroke rehabilitation in Pakistan and LMIC could offer an effective strategy for addressing the psychological needs of stroke patients, emphasizing a holistic approach to recovery. Future research should explore the long-term benefits of EFT and its applicability in diverse healthcare settings.